Novel Neuropathic Pain Mechanisms Associated With Allergic Inflammation - Fujii, Takayuki; Yamasaki, Ryo; Kira, Jun-ichi (Frontiers in Neurology, 2019)
Allergic diseases are associated with central and peripheral nervous system diseases such as autism spectrum disorders and eosinophilic granulomatosis with polyangiitis, which frequently causes mononeuritis multiplex. Thus, it is possible that patients with an atopic constitution might develop multifocal inflammation in central and peripheral nervous system tissues. In a previous study in Japan, we reported a rare form of myelitis with persistent neuropathic pain (NeP) in patients with allergic disorders. However, the underlying mechanism of allergic inflammation-related NeP remains to be elucidated. First, we analyzed the effect of allergic inflammation on the nociceptive system in the spinal cord. Mice with atopy showed microglial and astroglial activation in the spinal cord and tactile allodynia. In a microarray analysis of isolated microglia from the spinal cord, endothelin receptor type B (EDNRB) was the most upregulated cell surface receptor in mice with atopy. Immunohistochemical analysis demonstrated EDNRB expression was upregulated in microglia and astroglia. The EDNRB antagonist BQ788 abolished glial activation and allodynia. These findings indicated that allergic inflammation induced widespread glial activation through the EDNRB pathway and NeP. Second, we investigated whether autoantibody-mediated pathogenesis underlies allergic inflammation-related NeP. We detected specific autoantibodies to small dorsal root ganglion (DRG) neurons and their nerve terminals in the dorsal horns of NeP patients with allergic disorders. An analysis of IgG subclasses revealed a predominance of IgG2. These autoantibodies were mostly colocalized with isolectin B4- and P2X3-positive unmyelinated C-fiber type small DRG neurons. By contrast, immunostaining for S100β, a myelinated DRG neuron marker, showed no colocalization with patient IgG. Immunoprecipitation and liquid chromatography-tandem mass spectrometry identified plexin D1 as a target autoantigen. Patients with anti-plexin D1 antibodies often present with burning pain and thermal hyperalgesia. Immunotherapies, including plasma exchange, are effective for NeP management. Therefore, anti-plexin D1 antibodies may be pathogenic for immune-mediated NeP, especially under allergic inflammation conditions. Thus, allergic inflammation may induce NeP through glial inflammation in the spinal cord and the anti-plexin D1 antibody-mediated impairment of small DRG neurons.